Preparedness of Community Hospital Against COVID-19 - Prajapati, Ijendra; Kayastha, Gyan (Journal of Lumbini Medical College, 2020)
Government of Nepal (GoN) imposed a nationwide lockdown on 24th March, 2020 with an effort to limit the spread of novel corona virus which is responsible for corona virus disease (COVID-19). COVID-19 Nepal: Preparedness and Response Plan (NPRP) was implicated on April 2020 which stated Sukraraj Infectious and Tropical Disease Hospital (STIDH) in the capital, Kathmandu has been designated by the GoN as the primary hospital along with Patan Hospital and the Armed Police Forces Hospital in the Kathmandu Valley. The Ministry of Health and Population (MoHP) had requested the 25 hub and satellite hospital networks across the country; designated for managing mass casualty events; to be ready with infection prevention and control measures, and critical care beds where available.